Group Counseling with Psychodrama and Gurindam 12 Values to Enhance Empathy in Bullies - Raja Zulfikar; Zadrian Ardi; Yeni Karneli; Nurfarhanah; Ramdani (Universitas PGRI Yogyakarta, 2026)
Bullying in the school environment is a serious problem that has an impact on the social development and psychological health of students. The perpetrator's low empathy is one of the factors that strengthen aggressive behavior. Although psychodrama techniques have been known as an effective experiential counseling approach, their integration with local cultural values such as Gurindam 12 has not been extensively tested quantitatively, particularly in Indonesia. This study aims to test the effectiveness of group counseling with psychodrama techniques loaded with the value of Gurindam 12 in increasing the empathy of bullies. The study used a quasi-experimental design with a pretest-posttest control group. A total of 20 students with high levels of bullying and low empathy were selected through purposive sampling and divided into experimental (n=10) and control (n=10) groups. The instrument used was an adaptation of the Interpersonal Reactivity Index (α = 0.917). Data analysis was carried out using the Wilcoxon Signed-Rank and Kolmogorov-Smirnov Two-Independent-Samples tests. The results showed a significant improvement in the experimental group (mean from 115.3 to 181.0; N-Gain of 70.0 in the high category) compared to the control group (mean from 108.4 to 166.3; N-Gain of 57.5 in the moderate category), with significanta differences between-group difference (Z=2.236; p=0.003). These findings suggest that integrating cultural values into psychodrama effectively enhances empathy and supports student character building. Keywords: bullying, group counseling, gurindam 12, empathy, psychodrama